1996
DOI: 10.1021/cm950225m
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Structural, Textural, and Catalytic Properties of Montmorillonite Pillared with (GaAl12) and (AlAl12) Polyoxycations

Abstract: This paper reports the preparation of a pillared montmorillonite using the mixed oligomer [GaO 4 Al 12 (OH) 24 (H 2 O) 12 ] 7+ . Pillaring was performed with a starting solution having a molar ratio of Al 3+ /Ga 3+) 12, which is equivalent to the stoichiometric ratio of this polyoxycation. To determine the optimum conditions for obtaining the desired product, we varied the OH -/ (Al 3+ + Ga 3+ ) molar ratio in the range 1.5-2.5, which also produced variations in the pH of the oligomeric solution. The most favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 26 publications
0
15
0
2
Order By: Relevance
“…The possibility of making bifunctional Pt/PLS catalysts has been illustrated by using test reactions such as the hydroisomerization and hydrocracking of n-alkanes. [118][119][120][121][122][123][124] These studies, in general, showed that there is a direct correlation between the Brøn-sted acidity of the PLS and the hydroisomerization/ hydrocracking activity, and furthermore it is possible to achieve on these materials a good balance between hydrogenation-dehydrogenation and the cracking functions.…”
Section: Catalytic Activity Of Acid Plsmentioning
confidence: 99%
“…The possibility of making bifunctional Pt/PLS catalysts has been illustrated by using test reactions such as the hydroisomerization and hydrocracking of n-alkanes. [118][119][120][121][122][123][124] These studies, in general, showed that there is a direct correlation between the Brøn-sted acidity of the PLS and the hydroisomerization/ hydrocracking activity, and furthermore it is possible to achieve on these materials a good balance between hydrogenation-dehydrogenation and the cracking functions.…”
Section: Catalytic Activity Of Acid Plsmentioning
confidence: 99%
“…In recent years a number of researchers have investigated adsorption in synthetic pillared clays [1][2][3][4][5][6]. The synthesis of pillared clays was originally suggested by Barrer and McLeod [7], who inserted specific molecules into clay minerals to prop apart the aluminosilicate sheets, thereby producing larger pores than those found in natural clays.…”
Section: Introductionmentioning
confidence: 99%
“…Lempung terpilar Al mempunyai stabilitas termal yang cukup tinggi mencapai suhu 700°C [6]. Jarak antar lapis yang dihasilkan berkisar antara 12-18 Å yang dipengaruhi oleh kondisi sintesisnya [5].…”
Section: Pendahuluanunclassified
“…Kemungkinan lain yakni terjadi kerusakan pilar alumina oksida akibat kenaikan suhu. Hal ini didukung oleh penelitian [6,8] yang juga menghasilkan difraktogram yang menurun dengan kenaikan suhu yang menunjukkan bahwa pilar Al menurun dengan kenaikan suhu.…”
Section: Larutan Pemilar Dibuat Dengan Menghidrolisis Alcl3 Mengunakaunclassified